2014
DOI: 10.3233/nre-141148
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training in patients with Amyotrophic Lateral Sclerosis: A systematic review

Abstract: BACKGROUND: Amyotrophic Lateral Sclerosis is a neurodegenerative disease with rapid involvement of the inspiratory muscles, leading to respiratory insufficiency. Death often occurs by aspiration and pneumonia. Endurance-and strength therapy within ALS are discussed controversially. OBJECTIVE: To review the current literature to assess the efficacy of inspiratory muscle training for ALS. METHOD: Systematic review, using databases as PubMed, PEDro, Cochrane and Google Scholar. INTERVENTION: Inspiratory muscle tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 89 publications
0
8
0
1
Order By: Relevance
“…A systematic review 105 and a meta-analysis 106 have been published looking at the question of benefit of respiratory muscle training in ALS. The earlier systematic review 105 found no convincing evidence of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review 105 and a meta-analysis 106 have been published looking at the question of benefit of respiratory muscle training in ALS. The earlier systematic review 105 found no convincing evidence of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Amyotrophic Lateral Sclerosis Functional Rating Scale ALSFRSR (Cedarbaum et al., 1999), a score below 30 indicates a moderate presentation of the disease and was used to inform inclusion. Exercise is known to be contraindicated with chronic symptomatology (Eidenberger & Nowotny, 2014). Participants with a score above 30 were considered and judged on a case‐by‐case basis, this was because wheelchair users or those with swallowing or speech problems may have a score above 30, but could be capable of participation.…”
Section: Methodsmentioning
confidence: 99%
“…Two systematic reviews included studies lasting from 12 weeks to 32 months and investigating respiratory training in individuals living with MND, including: respiratory training muscle and yoga breathing technique. In one study, duration per session was 10 minutes, while other studies reported 10 to 15 repetitions per sessions, two to five times a day, every day (29,59).…”
Section: Respiratory Trainingmentioning
confidence: 99%